Managing hyperparathyroidism in hemodialysis: role of etelcalcetide - Eidman KE; Wetmore JB (International Journal of Nephrology and Renovascular Disease, 2018)
Keith E Eidman,1 James B Wetmore1,2 1Division of Nephrology, Hennepin County Medical Center, University of Minnesota, Minneapolis, MN, 2Chronic Disease Research Group, Minneapolis Medical Research Foundation, Minneapolis, MN, USA Abstract: Secondary hyperparathyroidism (SHPT) is common in patients receiving maintenance hemodialysis and is associated with adverse outcomes. Currently, SHPT is managed by reducing circulating levels of phosphate with oral binders and parathyroid hormone (PTH) with vitamin D analogs and/or the calcimimetic cinacalcet. Etelcalcetide, a novel calcimimetic administered intravenously (IV) at the end of a hemodialysis treatment session, effectively reduces PTH in clinical trials when given thrice weekly. Additional clinical effects include reductions in circulating levels of phosphate and FGF-23 and an improved profile of markers of bone turnover. However, despite being administered IV, etelcalcetide appears to be associated with rates of nausea and vomiting comparable to those of cinacalcet. Additionally, etelcalcetide, relative to placebo, causes hypocalcemia and prolonged electrocardiographic QT intervals, effects that must be considered when contemplating its use. Etelcalcetide likely has a role in treating hemodialysis patients with uncontrolled SHPT or with hypercalcemia or hyperphosphatemia receiving activated vitamin D compounds. However, its use should be at least partially constrained by consideration of the risk of hypocalcemia and resultant prolonged QT intervals in vulnerable patients. Because of its effectiveness as a PTH-reducing agent administered in the dialysis unit, etelcalcetide represents a potentially promising new therapeutic approach to the often vexing problem of SHPT in hemodialysis patients. However, whether its use is associated with changes in surrogate clinical end points, such as effects on rates of parathyroidectomy, fracture, vascular calcification, or mortality or on quality of life, remains to be studied. Keywords: chronic kidney disease, calcimimetic, parathyroidectomy